Mini VAWT Generator - Mat Zian@ Mat Zin, Ahmad Faiz; Hishamudin, Adam Haziq; Mohamad Ariff, Mohamad Aqmal; Azami, Muhammad Syahmi; Roslan, Muhammad Sufi; Taib, Ishkrizat (Multidisciplinary Applied Research and Innovation, 2025)
This project designs, fabricates, and tests a prototype of a Mini Vertical Axis Wind Turbine (VAWT) Generator for small-scale energy generation. This mini VAWT’s vertical blade design enables omnidirectional wind capture, enhancing reliability in variable wind conditions. Mechanical energy is converted into electricity via a shaft and spur gear system, stored in batteries, or used to power small appliances like light bulbs. The electrical system includes a battery management system, an AC-to-DC circuit, and a voltage regulator for stability. The prototype blades and shaft are 3D-printed using PLA material for cost-effectiveness and ease of fabrication. Testing shows the turbine generates 0.31 to 1.23 VDC at wind speeds of 1.4 to 7 m/s, successfully charging the integrated battery. This project demonstrates the potential of small-scale VAWTs as sustainable energy solutions for low-power applications, particularly in urban or remote areas. Future work will focus on material optimisation and efficiency improvements for broader implementation.